A review of the current hotel industry situation in Malaysia/ Gopinath Sangaran and Gobinath Selvanayagam - Sangaran, Gopinath; Selvanayagam, Gobinath (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
This review focuses on the hotel industries current situation and highlights the current state, capacity, strength, and vulnerabilities for the future after the pandemic times. The tourism development in Malaysia has paved way for the hotel industries development. These developments include Job opportunities, Infrastructure development, Tourism product development, and Education. However, there are vulnerabilities in the industry that consists of Homestays Models, Organisational Culture, Job satisfaction and turnover. The future for the hotel industry would depend on Industry 4.0 and Lean Management for their progress. Data were gather based on journal articles, tourism websites and professional consultancy websites. Based on this review the author offers and insight and a summary of what has been supported in the literature on the Hotel industry in Malaysia.